Child care practices associated with positive and negative nutritional outcomes for children in Bangladesh: a descriptive analysis - Kumar, Shubh K.; Naved, Ruchira T.; Bhattarai, Saroj (International Food Policy Research Institute, 1997)
This study attempts to identify characteristics of the existing child and the maternal care environment that could be used as a basis for designing policies and programs to improve the nutritional status of children. For the present study, all children between 6-18 months of age were selected from a nutrition survey of a cross section of 741 households conducted by the IFPRI Bangladesh Food Policy Project in February-March 1992. Information was obtained on feeding practices of infants and mothers, indicators of psychosocial care, and health and hygiene practices. In this study, information on child care practices obtained together with information from the original nutrition survey on maternal and child nutrition, individual food consumption, and household demographic and socioeconomic status was used. Children who exhibited the best growth status, holding age and income level constant, compared to the others in the same environmental setting, are identified as positive deviants. Those with the worst growth are categorized as negative deviants. Children falling in-between positive and negative deviants are labeled as median growers. Even though an increase in income was found to be associated with improving child nutrition, on average, this association was not very evident at the two tails of the nutrition status distribution, with household income of negative deviant children higher than for both the positive deviants and median growth children, implying a limited access or allocation of household income by mothers in these households, and the relevance of non-income factors. A selection of caring practices and indicators were identified for infant feeding, complementary feeding, maternal diet and health, psychosocial care, and health and hygiene practices.